Human rights tribune = Tribune des droits humains - Human Rights Internet.; University of Ottawa. Human Rights Research and Education Centre.; International Centre for Human Rights and Democratic Development. (Human Rights Internet, 1992)
Continued by: Human rights tribune (Ottawa, Ont. : Online)